Probing Electric Field Distributions in the Double Layer of a Single-Crystal Electrode with Angstrom Spatial Resolution using Raman Spectroscopy - Wen, Bao-Ying; Lin, Jia-Sheng; Zhang, Yue-Jiao; Radjenovic, Petar M; Zhang, Xia-Guang; Tian, Zhong-Qun; Li, Jian-Feng (Journal of the American Chemical Society, 2020)
The electrical double layer (EDL) is the extremely important interfacial region involved in many electrochemical reactions, and it is the subject of significant study in electrochemistry and surface science. However, the direct measurement of interfacial electric fields in the EDL is challenging. In this work, both electrochemical resonant Raman spectroscopy and theoretical calculations were used to study electric field distributions in the EDL of an atomically flat single-crystal Au(111) electrode with self-assembled monolayer molecular films. This was achieved using a series of redox-active molecules containing the 4,4′-bipyridinium moiety as a Raman marker that were located at different precisely controlled distances away from the electrode surface. It was found that the electric field and the dipole moment of the probe molecule both directly affected its Raman signal intensity, which in turn could be used to map the electric field distribution at the interface. Also, by variation of the electrolyte anion concentration, the Raman intensity was found to decrease when the electric field strength increased. Moreover, the distance between adjacent Raman markers was ∼2.1 Å. Thus, angstrom-level spatial resolution in the mapping of electric field distributions at the electrode–electrolyte interface was realized. These results directly evidence the EDL structure, bridging the gap between the theoretical and experimental understandings of the interface.